The challenges of green building implementation in Malaysia - Noor Azirhan , Sahat (2012)
The construction industry is one of the largest sector responsible for high-energy consumption, solid waste generation, global green house gas emissions, external and internal pollution, environmental damage and resource depletion. In order to overcome this problems, green building is being develop in Malaysia, especially government took drastic actions in promoting and emphasizing green building. This study covers the challenges of green building implementation in Malaysia. The objectives of the studies are to identify level of awareness of parties involved, to determine problems preventing the implementation and to analyzed the effect of green building implementation in Malaysia that conducted at Peninsular Malaysia, Sabah and Sarawak. The methodology of this study involved literature review, data collection by questionnaires and analysis of results using the Average Index Method. Through the literature review the level of awareness, problems preventing growth of green building and effects of green building implementation have been identified. Questionnaires were prepared according to the studies objectives and Were sent to developers, contractor, and building professionals around Peninsular Malaysia, Sabah and Sarawak. Based on the study, green building is widely understood by majority industry players in construction, yet the implementation is not being widely carried out. The numbers of green building carried out are relatively small compare to overall project carried out. Although, drastic action and plan have been taken to promote green construction in Malaysia, the issue preventing the implementation and emphasizing of green building have been studied to mitigate the failure. There are several recommendation have been proposed to mitigate the failure and encourage the implementation of green building in Malaysia.